Expectation-based teaching: an action research in English report writing/ Ai Kiat Teo..[et al.] - Teo, Ai Kiat; E.H. Voon, Grace; Voon, Boo Ho (Universiti Teknologi MARA, Kedah, 2013)
The concept of customer orientation in the field of marketing can be applied in teaching English. It is always necessary to understand students’ needs, discuss and share this information as well as respond to the information accordingly to improve students’ performance. This paper addresses the need for understanding the students’ needs and teaching accordingly to improve the quality of English report-writing. A proposed Expectation-based Teaching (EBT) approach was tested (n=79). The findings of the action research indicated that the students performed better when they understood what was expected of them in writing a statistical-based English report. The overall mean score of the students increased significantly after they were briefed and taught based on the expectations of the writing components. The content quality of their writing was much better than before. These trends were the same for samples with different demographic characteristics.